AI in the Delivery Room: Shaping the Future of Childbirth - Oleszczuk, Anna; Woźniak, Weronika; Pelczar, Patrycja; Skowron, Aleksandra; Kimber-Trojnar, Żaneta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2025)
Background. Artificial intelligence (AI) is defined as the application of advanced algorithms and machine learning techniques to analyze large amounts of data. Its use in medicine concerns areas such as medical images, laboratory test results, and patient medical histories. Thanks to its predictive capabilities, AI can also forecast the risk of diseases, identify patterns in data, and discover new relationships, which can lead to better healthcare, faster diagnoses, and more effective therapies. Aim. This study reviews current applications of artificial intelligence in obstetrics, highlighting its benefits in routine tests like ultrasound and its impact on IVF procedures. Material and methods. The studies cited in the presented review were selected from PUBMED.The oldest article is from 2017, while the most citations come from articles from 2023. The key words used for the search included: ‘artificial intelligence’ and ‘obstetrics’. Articles not written in English were excluded. Results. In obstetrics, artificial intelligence has applications in many examinations used on a daily basis, such as ultrasound or cardiotocography. In addition, it is also used, among other things, to analyse fetal heart echocardiography films and calculate the deviation from normal. Other uses of artificial intelligence can be seen in imaging methods such as MRI. The impact of this technology in the in vitro procedure should be noted as well. Conclusions. AI technology will possibly bring opportunities for better medical care in obstetrics. It will enable better diagnosis and more effective treatment. It also brings an opportunity for the development of better treatments for infertility in women.